A Holistic Overview of Agricultural Practices among CDIP Beneficiaries in Salimgonj Area: Current Status, Persistent Problems, and Promising Prospects - Nujhat Tabassum Safa; Mahbubur Rashid Ories (Research in Agriculture Livestock and Fisheries, 2024)
Agriculture is an essential industry in rural Bangladesh since it is the primary source of income for fifty percent of the workforce and eighty seven percent of families. Non-governmental organizations (NGOs) play an essential part in advancing sustainable development by providing assistance to communities in need and giving them the tools, they need to boost agricultural production, improve food security, and alleviate poverty. Centre for Development Innovation and Practices (CDIP), which is located in Bangladesh, runs microfinance programs with the goals of eradicating poverty and providing persons who are economically disadvantaged with financial security. The research project utilized a Mixed-method approach, with the CDIP beneficiaries participating in both Key Information Interviews (KII) and Focused Group Discussions (FGD) as part of the research. The efficiency of certain agricultural initiatives is hindered by obstacles such as limited technical skills, infrastructure limitations, and a lack of availability of high-quality seeds and irrigation facilities. Despite all of these obstacles, there are chances for CDIP beneficiaries to develop their agricultural practices. It has been demonstrated that the utilization of mobile agricultural consulting services and digital platforms can increase crop output while also ensuring financial security. It has also been established that collaboration among CDIP, government agencies, and local communities may increase infrastructure, which in turn leads to improved market access and economic development for agriculture beneficiaries. The research focuses on loan distribution in the Salimgonj area of Bangladesh and emphasizes how important it is to address persisting barriers to sustainable agricultural growth. Vol. 10, No. 3, December 2023: 277-284